Does picky eating behavior exist in university students? - Zulkefli, Nur Fadzlina; Khattak, Muhammad Muzaffar Ali Khan; Mohd Abu Bakar, Wan Azdie (IIUM Press, International Islamic University Malaysia, 2018)
The aim of this study was to assess picky eating behavior existence among university students. This was an observational cross sectional study design. The sample size was calculated by using single proportion formula based on the adult prevalence of picky eating of 28.7 % which gives a sample of ~ 324 students. However, 407 students online registered to participate out which 403 students responded. A set of questionnaire was posted online. The questionnaire contained three sections which are demographic information, determinants of picky eating behavior and normal eating behaviors. Furthermore, the students were categorized as non-picky eating behavior, moderate picky eating behavior, and extreme picky eating behavior. The statistical analysis carried out was mainly descriptive in order to determine the extent of picky eating behavior among the university students. Student t-test was used to find the differences between picky and non-picky eaters in terms of eating behaviors. Among the students possessing non picky eating behavior, moderate picky eating behavior and extreme picky eating behavior were 168 (41.69%), were 130(32.26%), 105(26.05%) respectively. On overall basis 235(58.31 %) of the students were having picky eating behavior. The present study revealed that picky eating behavior exists among the university students which need to be addressed.